Effect of heparin and related glycosaminoglycan on PDGF-induced lung fibroblast proliferation, chemotactic response and matrix metalloproteinases activity. Issue 2 (2000) - Sasaki, Masahiro; Kashima, Masayuki; Ito, Takefumi; Watanabe, Akiko; Sano, Masaaki; Kagaya, Manabu; Shioya, Takanobu; Miura, Mamoru
Abstract : Fibroblast migration, proliferation, extacellular matrix protein synthesis and degradation are the key events in various biological and pathological processes in pulmonary fibrosis. In addition, biopsy specimens from the lungs of patients with plumomary fibrosis show increased numbers of mast cells which have metachromatic granules containing heparin, histamin and proteases. Little is known about how these products influence pulmonary fibrosis. In the present study, we investigated the effect of heparin and related glycosaminoglycans on PDGF-induced lung fibroblast proliferation and chemotactic response in vitro . In addition, we examined the effect of heparin on both the induction of matorix metalloproteinases (MMPs) and MMPs activity in lung fibroblasts in vitro . Heparin, de-N-sulphated heparin but not heparan sulphate inhibited PDGF-induced lung fibroblast proliferation. In contrast, only heparin inhibited PDGF-stimulated human lung fibroblast chemotaxis. Negatively charged poly- L -gultamic acid had no effect on either fibroblast proliferation or chemotaxis. Thus the negative charge alone cannot account for the ant-proliferative and anti-chemotactic effects of heparin. Furthermore, heparin and heparan sulphate also had no inhibitory effect on induction of MMPs, including MMP-1 (interstitial collagenase), MMP-2 (gelatinase A) and MMP-9 (gelatinase B). Only heparin inhibited both MMP-1 and MMP-2/MMP-9 activity. Additionally, tissue inhibitor of metalloproteinase type 1 (TIMP-1) and type 2 (TIMP-2) inhibited PDGF-stimulated human lung fibroblast chemotaxis. The ability of heparin to inhibit fibroblast chemotaxis may account for the inhibitory effect of heparin on MMP activity. The above results suggested that heparin and related glycosaminoglycans differentially regulate PDGF-induced lung fibroblast proliferation, chemotaxis and MMPs activity and further that these effects may have a key role in extracellular matrix remodeling in inflammatory lung disease.